Covalent functionalization of boron nitride nanotubes: A brief review - Thang Quoc Huynh (Next Nanotechnology)
Boron nitride nanotubes (BNNT) have garnered significant attention recently due to their unique properties, such as high thermal conductivity, excellent mechanical strength, neutron shielding capacity, and chemical stability. However, their inherent hydrophobic nature and poor solubility in most solvents hinder their widespread application in various fields. Covalent functionalization of BNNT offers a promising solution to enhance their dispersibility, tailor their properties, and enable their integration into diverse applications. This work examines advancements in covalent functionalization strategies to improve BNNT dispersibility and broaden their applicability. Key aspects explored include identifying effective functionalization methods, understanding their impact on BNNT structure, and evaluating current challenges. Various approaches, such as defect-site functionalization, defect generation, and direct functionalization, are analyzed. Therefore, this study will provide a systematic evaluation of emerging reactions, current limitations, and potential breakthroughs in BNNT modification.